Geospatial Assessment of Healthcare Accessibility and Equity in Qatar in Preparation for the 2022 FIFA World Cup - Ammar Abulibdeh (15785928) (2024)
Accessibility to healthcare is one of the significant components of social determinants of public healthcare and is integral to societies’ overall well-being and economic prosperity. This study intends to assess changes in spatial distributions and accessibility of healthcare services within Qatar for 2010–2020, specifically concerning preparation for the 2022 FIFA World Cup. Assessment of the healthcare infrastructure is made using various techniques within a Geographic Information Systems (GIS) framework, like kernel density estimation, network analysis, and proximity analysis. The results show that access to healthcare has significantly improved, especially in urban centers such as Doha, besides a significant reduction in the length one travels to access healthcare facilities. However, despite improvements, many areas outside Doha still lag, requiring further investment in strategic planning. This study underscores how effective the health policies in Qatar and the Qatar National Master Plan (QNMP) have been in furthering principles of equity in access to healthcare services. The policy implications are that healthcare service planning should be integrated with urban development and transport networks for sustainable improvement in healthcare access. Thus, investment in infrastructure, strategic planning of locations, and addressing residual disparities are crucial for the long-term healthcare equity and system resilience of Qatar’s healthcare system. Other Information Published in: Journal of Geovisualization and Spatial Analysis License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s41651-024-00206-z